2015
DOI: 10.1016/j.aninu.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modulation of DNA methylation by nutrition and its mechanisms in animals

Abstract: It is well known that phenotype of animals may be modified by the nutritional modulations through epigenetic mechanisms. As a key and central component of epigenetic network, DNA methylation is labile in response to nutritional influences. Alterations in DNA methylation profiles can lead to changes in gene expression, resulting in diverse phenotypes with the potential for decreased growth and health. Here, I reviewed the biological process of DNA methylation that results in the addition of methyl groups to DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 122 publications
(150 reference statements)
3
88
2
4
Order By: Relevance
“…As abovementioned, an increasing number of studies in rodents have demonstrated that the nutritional stimuli may alter the phenotype of animals through epigenetic mechanisms [48] as well as these epigenetic alterations can be transmitted through at least three generations in mammals [49]. Here, we found a higher degree of global 5-mC and a diminution in 5-hmC, which paralleled with changes in their enzymatic machinery such as DNMTs and TETs, in the hippocampus of the offspring.…”
Section: Discussionsupporting
confidence: 67%
“…As abovementioned, an increasing number of studies in rodents have demonstrated that the nutritional stimuli may alter the phenotype of animals through epigenetic mechanisms [48] as well as these epigenetic alterations can be transmitted through at least three generations in mammals [49]. Here, we found a higher degree of global 5-mC and a diminution in 5-hmC, which paralleled with changes in their enzymatic machinery such as DNMTs and TETs, in the hippocampus of the offspring.…”
Section: Discussionsupporting
confidence: 67%
“…Supplementation with methyl donors including FA has been reported to alleviate the effects of adverse intrauterine environment [25]. In only a few studies, however, DNA methylation status has been examined.…”
Section: Plos Onementioning
confidence: 99%
“…Evidences showing a link between early life nutrition and epigenetics have been shown and reviewed by several authors (Dolinoy et al 2006;Kucharski et al 2008;Vickers 2014;Zhang 2015;Marandel et al 2016). This knowledge can be extremely useful for aquaculture, where feeding plays a major role for a sustainable production.…”
Section: Epigenetics In Aquaculturementioning
confidence: 98%